Financial Distress and Indonesian Family Resilience during the COVID-19 Pandemic: A Case Study of a Muslim Family in Yogyakarta - Amilia, Fatma (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2023)
The objective of this study is to find evidence of the relationship between financial distress and family resilience and to examine the factors driving such family resilience in Indonesia during the COVID-19 epidemic. The study revealed some significant variables in family resilience, namely maintaining a positive outlook, family connectivity, and facing difficulties. Additionally, the study showed that certain variables had no significant effect on family resilience, such as family spirituality (SK), ability to understand difficulties (KMK), and financial pressure index (ITK). These findings document that family resilience is not solely caused by financial problems but is more based on psychological factors. Originality/Value: This paper contributes to the development of theoretical aspects related to family resilience and financial inclusion.